Pemanfaatan Residu Vermikompos dan Aplikasi Vermiwash terhadap Pertumbuhan, Hasil dan Pigmentasi Tanaman Selada Merah (Lactuca sativa L. var Crispa) yang Ditanam pada Media Hidroganik - Khusnah Munawaroh; Nurhidayati Nurhidayati; Istirochah Pujiwati (AGRONISMA, 2021)
Lettuce is one type of vegetable that is used for its leaves or often referred to as leaf vegetables. Selda also has a high nutritional content. Production of red lettuce is also still not able to meet the demand. This study aims to determine the interaction between vermicompost residue and vermiwash application on the growth, yield and color pigmentation of red lettuce. This research was conducted at a plastic house on Jl. MT. Haryono, Dinoyo, Lowokwaru Malang District with an altitude of Â± 550 meters above sea level, air temperature ranging from 20 oC - 35 oC, which was carried out from October 2020 - December 2020. The design used was a Factorial Randomized Block Design (RAK) with Control. Factor 1 residual dose of vermicompost with 3 levels, namely: V1 = 100 g/pot Vermicompost, V2 = 200 g/pot Vermicompost and V3 = 300 g/pot Vermicompost. Factor 2 Concentration of Vermiwash with 3 levels, namely: K1 = 200 ml/L Vermiwash, K2 = 400 ml/L Vermiwash and K3 = 600 ml/L Vermiwash. Each treatment was repeated 3 times with 4 samples and 1 treatment using AB Mix nutrition (control). From the research, it was found that the residual dose of vermicompost and the concentration of vermiwash had a significant effect on plant growth and yield, except for the variables of plant height, root fresh weight and root dry weight. In general, the best treatments were V2K3 (200 g/pot Vermicompost + 600 ml/L Vermiwash) and V3K1 (300 g/pot Vermicompost + 200 ml/L Vermiwash). In observing leaf color pigmentation, visual determination of leaf color showed differences between treatments and controls and between replicates. Differences that occur between treatments with controls and between replications can be caused by several things, including the nutritional content given and the lighting received.